Use of weight loss agents in the treatment of obesity: comparison of adverse effects in the use of orlistat versus sibutramine (Research, Society and Development, 2022)
The objective of this study was to analyze the scientific evidence in the Scientific Electronic Library Online (SCIELO), Latin American Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online - (MEDLINE/PUBMED) databases, making a comparison of adverse effects in the use of orlistat versus sibutramine. The research method used was an integrative literature review with a qualitative approach. After selecting 100 articles, two criteria were used, namely: inclusion criteria (articles published from 2014 to 2022; articles published in Portuguese; original and review articles on the subject) and exclusion criterion (duplicated articles in the databases); primers, books, notebooks, handouts, dissertations, theses and course conclusion works). Afterwards, 10 articles were selected for the elaboration of this work, they were presented in table form and discussed in the sequence. Given this scenario, it was concluded that anorectic drugs can cause several adverse effects, so it is always necessary to carry out the treatment with the follow-up of a qualified professional, since the irrational use can be harmful to the patient's health.